Evolution in Computed Tomography. Issue 9 (September 2015) - Lell, Michael M.; Wildberger, Joachim E.; Alkadhi, Hatem; Damilakis, John; Kachelriess, Marc
<x xml:space="preserve">Abstract</x> Abstract The advent of computed tomography (CT) has revolutionized radiology. Starting as head-only scanners, modern CT systems are now capable of performing whole-body examinations within a couple of seconds in isotropic resolution. Technical advancements of scanner hardware and image reconstruction techniques are reviewed and discussed in their clinical context. These improvements have led to a steady increase of CT examinations in all age groups for a number of reasons. On the one hand, it is very easy today to obtain whole-body data for oncologic staging and follow-up or for trauma imaging. On the other hand, new examinations such as cardiac imaging, virtual colonoscopy, gout imaging, and whole-organ perfusion imaging have widened the application profile of CT. The increasing awareness of risks associated with radiation exposure triggered the development of a variety of dose reduction techniques. Effective dose values below 1 mSv, less than the annual natural background radiation (3.1 mSv/year on average in the United States), are now routinely possible for a number of dedicated examinations, even for coronary CT angiography.